Madness at the ‘gates of hell’ - Abd Razak, Dzulkifli (2006)
"We are dealing with a ruthless, cynical, cruel enemy, one of the most monstrous terror organisations this world has known." This statement was directed at the Lebanonbased Hizbollah by its adversary in a CNN report recently. But it is like the pot calling the kettle black as evident by the barbaric attacks on the Lebanese people. Even the Security Council, in attempting to find a ceasefire between Israel and Hizbollah, warns that continued fighting could have "grave consequences". No place better illustrates the case than Qana, a coastal town east of Tyre, in southern Lebanon. The fact that the Security Council expressed "extreme shock and distress" at the bombing of Qana and offered its condolences for the deaths underscores how brutal the incident was.